Percepção gráfica de rótulos de cerveja. Quais fatores são relevantes no processo de percepção. - Farneda, Carlos Estevan (Universidade do Vale do Rio dos Sinos, 2011)
The aim of this work is to graphically analyze different craft beer labels in order to understand how design has been used to build those brands. First of all 10 labels will be presented individually for 10 people who will have to answer which one is more visual pleasant and which one is less pleasant. On a second moment the three most preferred and the three most rejected labels will be analyzed following the criteria raised in the theoretical research.
Keywords: Cervejas artesanais; Rótulos; Design; Análise; Analyze; Labels; Craft beers